Meta-Analysis the Effect of Sensory Integration Therapy on Sensoric and Motoric Development in Children with Autism Spectrum Disorder - Fitriyaningsih, Ayu; Dewi, Yulia Lanti Retno; Adriani, Rita Benya (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: It is estimated that 90% of children diagnosed with ASD will show impaired sensory processing. Children with sensory processing problems present with delayed motor development which is caused by an underlying disorder in their ability to interpret sensations. Sensory integration therapy is one of the therapeutic methods to overcome sensory and motor problems. This study aims to estimate the effect of sensory integration therapy on sensory and motor development in children with autism spectrum disorders.Subjects and Method: This research was conducted using a systematic review study design and a meta-analysis conducted with PRISMA flow diagrams. The article search process was carried out between 2011-2021 using databases from PubMed, Science Direct, AJOT, Springer Link, and Google Scholar. The keywords used are “sensory integration” OR “sensory integration therapy” OR “ayres sensory integration” OR “sensory intervention” OR “sensory stimulation” AND “sensory processing” OR “sensory skills” OR “sensory system” AND “motor skills ” OR “motor developmental” AND “autism spectrum disorder” OR “autism”. Based on the database, there were 16 articles that met the inclusion criteria. The study design used was a Randomized Control Trial (RCT). The analysis was carried out using RevMan 5.3 software. Results: The meta-analysis is of 16 articles consisting of the continents of Asia, America, and Australia. Results showed that sensory integration therapy improved sensory development (SMD = 0.14; 95% CI -0.64 to 0.92; p = 0.73) and motor development (SMD = 0.42; 95% CI -0.27 to 1.11; p = 0.24). Conclusion: Sensory integration therapy did not significantly improve sensory and motor development in children with autism spectrum disorders.